Evaluación del efecto del agua magnetizada en plantas de amaranto (Amaranthus caudatus) variedad iniap-alegría en la etapa fenológica de crecimiento en Salache- Cotopaxi. - Chicaiza Toapanta, Jhonny Bladimir (2020)
The research was conducted at Salache Experimental Academic Center of the Technical University of Cotopaxi, within the research projects of the Greenhouse Smart and Andean Grains; at a height of 2733 m. where the general objective were: To evaluate the effect of magnetised water in plants of (Amarantus caudatus) variety INIAP- Joy in the phenological stage of growth (25 days), the specific objectives were: To determine the net demand of the magnetised water; Analyse the changes in chemical parameters that occur in the magnetised water and in the substrate used; Characterise agronomic behaviour of species. A Random Complete Block Design with 4 treatments and 20 experimental units was applied. Magnetised water was supplied at 3 intensities, (T1: 1000 gauss neodymium magnet; T2: 2 magnets (one neodymium and one mineral 3000 gauss, T3 magnets (1 neodymium magnet plus two mineral magnets) 5000 gauss) and a witness...